REIMAGINING WOMEN IN KANTHAPURA: A FEMINIST ANALYSIS OFNATIONALIST DISCOURSE - Dr. Sunita Rani Mehra (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
This research investigates into Raja Rao’s Kanthapura, exploring the construction of women characters within the nationalist discourse and employing feminist theories to analyze their roles. Despite the novel’s emphasis on mass movement over individual characterization, Rangamma, Ratna, and Achakka emerge as intricately delineated figures. Rangamma, an educated woman challengingtraditional norms, becomes a leader inspired by Gandhi’s ideals. Ratna, a child widow, defies societalexpectations, actively participating in the Gandhian movement. Achakka, the narrator, embodies collective female response to Gandhi’s call, representing a broader section of Kanthapura’s women. Itpositions Kanthapura within the context of Indian nationalism, utilizing Bhabha’s theory to scrutinizepolitical representations of women during the 1930s. It examines the novel’s demystification to uncover challenges faced by stereotyped Indian women and their role in shaping national identity. Kanthapura, reflecting Vedic Hindu ideals, addresses historical consciousness and the construction ofauthentic narratives during colonial India. The narrative explores the paradoxical nature of nationalist sentiments, sometimes aligning with European accounts, highlighting political desirability, and contributing to a unified Indian identity